When cooling is worse than warming: investigations into the thermal tolerance of an endemic reef fish, Boopsoidea inornata. Issue 2 (3rd April 2021) - Allison, C; Muller, C; Childs, A-R; Froneman, W; Bailey, LA; Potts, WM
Abstract : Recent investigations suggest that global warming is likely to alter temperature regimes along the southeastern coastline of South Africa through the increased frequency of upwelling events. Identifying thermal thresholds is fundamental in predicting the response of marine ectotherms to rapidly changing ocean temperatures. The aim of this study was to determine the thermal tolerance of the endemic sparid Boopsoidea inornata . To achieve this, 20 wild fish were captured from near Noordhoek in Gqeberha (Port Elizabeth). The fish were exposed to laboratory-simulated upwelling and heat-plume conditions until sublethal endpoints were identified to estimate the critical lower (CTmin ) and critical upper (CTmax ) thermal limits, respectively. During the simulated cooling or heating events, the opercular beat (OB) rates were recorded, their sublethal endpoints (loss of equilibrium) were identified, and their CTmin and CTmax were estimated. Breakpoint analyses of the OB rates identified the lower and upper thermal stress limits to occur at an average of 9 °C and 25 °C, respectively. The CTmin was estimated to be 7.8 °C and the CTmax 30 °C. When compared with in situ temperatures, these limits suggest that B. inornata is susceptible to small reductions in the minimum temperature. Given that the frequency and magnitude of upwelling events are expected to increase in response to global warming, this may have significant consequences for this and other sympatric, resident species.